Modern concepts of electronic textbook in teaching a foreign language (Eurasian Journal of Philology Science and Education, 2022)
The article is devoted to the study of the specifics of an electronic textbook on a foreign language, which is considered as the newest type of educational book that requires the development of theoretical and practical issues of its creation. The informatization of the educational process contributes and stimulates the change in the content of methods, approaches, aspects and forms of language teaching, where new technologies effectively organize the cognitive / cognitive activity of students and are based on the expanding possibilities of presenting educational, linguistic-cultural, and other information. An organic component of a traditional textbook is the new models of electronic educational publications in a foreign language, which enhance the motivation for learning the language with the novelty and modernity of the form of acquiring knowledge, and familiarity with the linguistic picture of the world. Multimedia programs contribute to teaching creative writing as a form of written communication. Electronic textbooks have the status of legality and are supported at the state level, and are used with multimedia technologies to improve the quality and motivational level of educational material presentation. The scientific problem of using modern information multimedia technology makes it possible to increase the communicative possibilities of enriching the content and presenting material when teaching a foreign language. The results of the study are a generalization of issues related to electronic manuals that have systematized information of a scientific and applied nature, and some mandatory components and basic principles for the creation and use of an electronic textbook are presented in the work.